Liver transplant outcome of cirrhotic patients treated with coronary stenting and early discontinuation of dual antiplatelet therapy. (March 2023) - Saracco, M.; Lavezzo, B.; Tandoi, F.; Calleri, A.; Manuli, C.; Giorgi, M.; Panio, A.; Ottobrelli, A.; Balagna, R.; Romagnoli, R.; Martini, S.
Abstract : Background: Significant coronary artery disease (CAD) should be treated with percutaneous revascularization in pre-liver transplant (LT) work-up. New-generation drug-eluting stents (DES) allow early discontinuation of dual antiplatelet therapy (DAPT). We aimed to describe pre-LT management and early post-LT outcome of our patients with CAD who underwent Percutaneous Coronary Intervention (PCI). Methods: We enrolled all patients transplanted in our Centre from 01/2018 to 04/2022 who underwent pre-LT cardiac catheterization (CATH). Stenosis ≥50% in a major-vessel or stenosis ≥70% in a moderate-sized branch vessel indicated significant CAD. Results: Among 638 adult patients who received LT, 33 underwent pre-LT CATH (5%) due to previous history of obstructive CAD (18%), positive noninvasive stress-test (61%), inconclusive noninvasive test (15%) or CAD symptoms (6%). CATH showed normal coronaries in 6/33 (18%), non-obstructive CAD in 15/33 (46%) and significant CAD in 12/33 (36%). These 12 patients were all male, median age 64 years, 75% diabetics, 83% smokers, median BMI 26kg/m 2 and underwent PCI with single (6/12) or ≥ 2 coronary arteries stenting (6/12). Patients received 31 days (IQR 31-41) of DAPT (clopidogrel+cardioaspirin), followed by aspirin monotherapy; anemia was a concern, without pre-LT major bleeding. Registration on the LT waiting list and LT occurred after 14 days (7-87) and 77 days (12-172) respectively from DAPT discontinuation. The median number of red blood cell units transfused during LT was 5 (2-7). At the end of LT, median arterial lactate and noradrenaline requirement were 1.9 mmol/L and 0.13 γ/Kg/min (Table 1 ). After a median follow-up of 321 days from LT: patient #1 experienced acute heart failure at month 4 th (EF 35%), following major gastrointestinal bleeding (hemoglobin 4.2 g/dL); CATH was unchanged; patient improved with blood transfusion (EF at discharge 45%). Conclusion: Coronary DES revascularization and early clopidogrel discontinuation was safe in cirrhotic patients with significant CAD and allowed timely LT.